Análise da lignina e dos polifenóis da aroeira-preta (astronium urundeuva) - Queiroz, Carla Regina Amorim dos Anjos (2001)
This work is based upon milled wood lignin (MWL) and phenolic compounds of the wood from Aroeira-Preta {Astronium urundeuva) harvested in the cerrado (savannah) in Triângulo Mineiro. At first, the milled wood lignin was extracted with solvents (benzene, ethanol/benzene 2:1, sodium hydroxide 0,1 N, chloroform, and acethone/water 9:1) in order to isolate the lignin. The obtained MWL was analyzed by wet assays to find out the functional groups (as methoxylic group determination), phenolic and aliphatic hydroxyls, a-O-4 and 0-0-4 linkages, carbonyls, oxidation using nitrobenzene, minimum formula); by spectroscopic methods (as ultraviolet, Fourier Transformed Infrared and 13C and *H Nuclear Magnetic Resonance) and chromatographic (as Gel Permeation Chromatography and High Performance Liquid Chromatography) that did the quantification and characterization of these groups possible. Besides, a quantitative study upon celluloses, hemicelluloses and extractives were made, fulfilling the study of this wood. The phenolic study was based on acetone/water and methanol/water extracts. The total phenols and proanthocyanidins leveis were evaluated with these extracts. This study concludes that this wood has a high extractive levei, high conjugated phenolics hydroxyls levei and possibly its MWL is condensed with polyphenolic extractives. Although many problems have arisen in the study of the proposed vegetal material, this work has much Chemical information that certainly will contribute for a better management of brazilian natural resources.